Cooperation between subunits is essential for high-affinity binding of N-acetyl-D-hexosamines to dimeric soluble and dimeric cellular forms of human CD69 - Kavan, Daniel; Kubícková, Monika; Bílý, Jan; Vanek, Ondrej; Hofbauerová, Katerina; Mrázek, Hynek; Rozbeský, Daniel; Bojarová, Pavla; Kren, Vladimír; Zídek, Lukás; Sklenár, Vladimír; Bezouska, Karel (Biochemistry, 2010)
CD69 is an earliest lymphocyte activation antigen and a universal leukocyte triggering molecule expressed at sites of active immune response. The binding of GlcNAc to the dimeric human CD69 was followed by equilibrium dialysis, fluorescence titration, and NMR. Clear cooperation was observed in the high-affinity binding (K(d) = 4.0 x 10(-7) M) of the carbohydrate to two subunits of the dimeric CD69 (Hill coefficient 1.94). A control monosaccharide ManNAc was not bound by human CD69, and both monosaccharides had no effects on the structure of the receptor. However, a monomeric CD69 obtained by mutating Q93 and R134 at the dimer interface exhibited a much lower affinity for GlcNAc (K(d) = 1.3 x 10(-5) M) and no cooperativity (Hill coefficient 1.07). Perturbation of the dimer interface resulted in a severe impairment of the signaling ability of cellular CD69 when cross-linked with an antibody or with a bivalent high-affinity N-acetylhexosamine dimer-based ligand. The availability of stable preparations of soluble CD69 receptor with well-documented ligand binding properties will be beneficial for immunological experiments evaluating the role of this antigen in the complex environment of the immune system. Moreover, such preparations in combination with efficient ligand mimetics able to both activate CD69(+) lymphocytes and to block undesired hyperactivation caused by other cellular ligands will also become indispensable tools in explaining the exact role of the CD69 antigen in the interaction between the tumor cell and the effector natural killer lymphocyte.
Keywords: Models, Molecular; vztahy mezi strukturou a aktivitou; hexosaminy; Protein Subunits; Humans; podjednotky proteinů; dimerizace; Structure-Activity Relationship; Jurkat buňky; diferenciační antigeny T-lymfocytů; Binding Sites; vazebná místa; CD antigeny; Ligands; molekulární modely; Antigens, CD; Lectins, C-Type; ligandy; lektiny typu C; Antigens, Differentiation, T-Lymphocyte; Hexosamines; lidé; Jurkat Cells; Dimerization